A Heatmap Approach for Master Data Management Programs - Ericsson, AnnMarie; Berndtsson, Mikael (Journal of Information Systems and Technology Management, 2022)
Master data management programs are large by nature since the aim is to provide the entire enterprise with a shared trusted view of the organisation’s most critical data assets. In this paper, we present what dimensions and activities a master data management program in a large organisation should consider and how to monitor such a program once it is up and running. A heatmap approach is used to visualize the inherent complexity of a master data management program. Our approach is derived from participating in four different master data management programs in four different global organisations during 2007-2020.